Human papillomavirus (HPV) genotypes present in cervical biopsies with histologically confirmed high-grade dysplasia, and a negative Cobas high-risk HPV test result : a thesis presented in fulfilment of the requirements for the degree of Master in Health Science at Massey University, Manawatu, New Zealand - Monk, Taylor (Massey University, 2021)
The prevalence of cervical dysplasia and cancer has decreased ever since the introduction of cytology screening and recently, primary HPV testing. However, there have been incidences of histologically proven high-grade cervical dysplasia with a corresponding negative primary high-risk HPV test in New Zealand. Therefore, the first aim of the thesis was to determine whether HPV is in fact present in cases with histologically confirmed high grade cervical dysplasia and a corresponding negative high-risk HPV result from the Roche Cobas HPV test. The second aim was to then determine the HPV genotype and viral load present in the samples to help to determine if the Cobas testing identified the sample incorrectly as negative due to issues with assay sensitivity (viral load) or specificity (HPV genotype). The results of the study initially identified the presence of low-risk HPV Type 6 DNA in three of the 16 samples. As a result, a qPCR assay was designed to select for HPV Type 6 to determine whether more of the samples contained HPV Type 6 DNA. It was found that seven samples contained only HPV Type 6 DNA, one contained only HPV Type 16 DNA and co-infections of both types 6 and 16 were identified in four of the samples. Three samples also contained a co-infection of either HPV Type 6 or 16 and an unknown HPV type. Quantification of HPV viral load was completed for the samples which ranged from 9.01 x 10⁵ copies/µL to 8.18 x 10¹⁰ copies/µL and it was determined that viral load did not correlate with CIN grade. The research conducted in this thesis was the first New Zealand study to identify HPV Type 6 in samples containing high-grade cervical dysplasia. Further research will be required on the prevalence of HPV Type 6 in New Zealand and whether these samples may progress to cancerous lesions or if they will spontaneously regress.
Figure 1.1 (=Doorbar et al., 2012 Fig 2B) was removed for copyright reasons but may be accessed via its source.
Keywords: 320705 Medical virology